2022
DOI: 10.1002/lary.30489
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Reflux Symptom Score versus Reflux Symptom Index in screening laryngopharyngeal reflux

Abstract: ObjectivesTo compare the screening value of the Reflux Symptom Score (RSS) and the Reflux Symptom Index (RSI) for laryngopharyngeal reflux (LPR).MethodsAll included patients attending the Department of Otolaryngology at the Sixth Medical Center of the PLA General Hospital from February 2022 to August 2022, completed the RSS and the RSI and underwent 24‐hour hypopharyngeal‐esophageal multichannel intraluminal impedance‐pH (24 h HEMII‐pH) monitoring. The results of 24 h HEMII‐pH were used as a diagnostic criteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…While the RSI investigates nine common symptoms in patients, the RSS questionnaire incorporates uncommon laryngeal symptoms and respiratory and gastrointestinal‐related symptoms. Our previous study showed that the RSS questionnaire had a higher kappa value than the RSI 8 . In this study, the RSS questionnaire still showed a high kappa value and AUC value.…”
Section: Discussionmentioning
confidence: 40%
See 4 more Smart Citations
“…While the RSI investigates nine common symptoms in patients, the RSS questionnaire incorporates uncommon laryngeal symptoms and respiratory and gastrointestinal‐related symptoms. Our previous study showed that the RSS questionnaire had a higher kappa value than the RSI 8 . In this study, the RSS questionnaire still showed a high kappa value and AUC value.…”
Section: Discussionmentioning
confidence: 40%
“…Twenty‐four hours of HEMII‐pH monitoring was performed on each included patient. The HEMII‐pH procedures have been described in previous the publication 8 . A proximal reflux event was defined as an episode in which reflux reached the 2 impedance sensors in the hypopharynx and a diagnosis of LPRD was made when more than 1 proximal reflux event occurred 11 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations